HGG-31. UNIQUE BIOLOGICAL CHARACTERISTICS OF RADIATION-INDUCED GLIOMAS. (4th December 2020) - Váňová, Kateřina; Vícha, Aleš; Krsková, Lenka; Zámečník, Josef; Malinová, Běla; Sumerauer, David; Mišove, Adéla; Libý, Petr; Zápotocký, Michal
Abstract: Radiation-induced gliomas (RIGs) are the most common secondary solid tumours with very unfavourable prognosis. We aimed to describe different clinical and molecular biological characteristic of RIGs from primary gliomas. We reviewed clinical data of ten patients with RIGs. In patients with available samples, we used the whole genome methylation array and performed targeted sequencing for specific mutations. Between 2000–2018, we diagnosed RIG in 10 patients (M/F 2/8) aged 5–12 years at primary diagnosis of different solid tumours and acute leukaemia. These patients developed RIG with a median 9.5 years (ranging 3–31) after primary diagnosis. Eight patients died within 1 year after diagnosis of RIG and 2 patients are still alive more than 4 years from this diagnosis. According to Heidelberg DNA methylation-based classification, most RIGs belong to the IDH-wild type glioblastoma subclass midline which biologically corresponds to diffuse midline glioma (DMG). However, compared to primary DMGs they do not carry the characteristic H3K27M mutation. One patient developed anaplastic ganglioglioma with BRAF-V600E mutation and methylation profile identical to pleomorphic xanthoastrocytoma (alive for 4 years after diagnosis of RIG). In half of the patients from the group DMGs IDH wild type, examined by methylation array, PDGFRA amplification was found. Our data shows that most RIGs are midline IDH-wild type glioblastomas with poor prognosis that are biologically different from primary DMGs. PDGFRA amplifications are potentially targetable by kinase inhibitors in order to order to prognosis of these patients.